2016
DOI: 10.1177/0194599816634616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Fibrin Sealant on Skin Graft Tissue Adhesion in a Rodent Model

Abstract: There is a significant difference in the adhesion strength of skin grafts to the wound bed in the early postoperative period of the 2 groups. In areas of high mobility, using the fibrin sealant can keep the graft immobile during the critical phases of early healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Adhesive glue provides additional mechanical stability. In a rat model, a thin layer of fibrin glue was associated with greater adherence strength determined by the amount of force required to sheer the graft from the wound on postoperative days 1 to 3 33 . Several studies show that use of glue is associated with lower rates of hematoma or seroma 34,35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesive glue provides additional mechanical stability. In a rat model, a thin layer of fibrin glue was associated with greater adherence strength determined by the amount of force required to sheer the graft from the wound on postoperative days 1 to 3 33 . Several studies show that use of glue is associated with lower rates of hematoma or seroma 34,35 .…”
Section: Resultsmentioning
confidence: 99%
“…In a rat model, a thin layer of fibrin glue was associated with greater adherence strength determined by the amount of force required to sheer the graft from the wound on postoperative days 1 to 3. 33 Several studies show that use of glue is associated with lower rates of hematoma or seroma. 34,35 From a patient perspective, glue is a useful aid for fixation in sensitive areas, reducing pain associated with staples or sutures.…”
Section: Retrospective Cohort Comparison (Iii)mentioning
confidence: 99%
“…Perez-Guisado et al recommended the use of fibrin glue to increase the possibility of skin graft survival [7]. Also, Balceniuk et al concluded that the fibrin glue used in skin grafting techniques helps in minimizing graft loss and lowers the rate of complications [8]. Butts et al reported significantly lower rates of skin graft loss while using fibrin glue [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Risk of complications in STSG placement vary based on patient demographics, comorbidities, and recipient graft site. 21 However, recent reports exploiting FG’s adherent properties for skin graft fixation are increasing, especially in animal research 2226 and clinically in burn patients. 2729 These clinical studies, although small in quantity, have reported positive outcomes with fewer graft loss and a decrease in hospital stay.…”
Section: Discussionmentioning
confidence: 99%